PENGARUH BEBAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL PUSKESMAS MAYANGAN JOGOTOTO - Wasis (Universitas Sains dan Teknologi Komputer, 2022)
The purpose of this study is to understand and explain the influence of workload and work ability related to the performance of medical personnel of the Mayangan Jogoroto Health Center. In this study, a quantitative approach will be used. The sample used was 42 medical personnel employees who were Civil Servants, the sample was saturated with the method chosen for sampling that will be used in this study. In collecting data, you will use the method by distributing questionnaires or questionnaires. In this study will use Likert Scale measurements This research will use the method of multiple linear regression analysis. The results showed that workload negatively affects the performance of doctors, midwives, and nurses who have the status of Civil Servants at the Mayangan Jogororo Health Center. Work ability has a positive effect on the performance of doctors, midwives, and nurses who have the status of Civil Servants at the Mayangan Health Center.